Guest

Arg(z)-Arg(-z)=Arg(-1)=pi but Arg(-z)-Arg(z)=Arg(-1) is not equal to pi Solve mathematically not graphically

Arg(z)-Arg(-z)=Arg(-1)=pi but Arg(-z)-Arg(z)=Arg(-1) is not equal to pi Solve mathematically not graphically

Grade:Upto college level

1 Answers

Aniket Patra
48 Points
11 years ago

Dear Nehal,they are not at all the same expression..

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free